Platelet-Derived Extracellular Vesicles Increase Col8a1 Secretion and Vascular Stiffness in Intimal Injury - Bao, Han; Li, Zi-Tong; Xu, Lei-Han; Su, Tong-Yue; Han, Yue; Bao, Min; Liu, Ze; Fan, Yang-Jing; Lou, Yue; Chen, Yi; Jiang, Zong-Lai; Gong, Xiao-Bo; et al. (Frontiers in Cell and Developmental Biology, 2021)
The arterial mechanical microenvironment, including stiffness, is a crucial pathophysiological feature of vascular remodeling, such as neointimal hyperplasia after carotid endarterectomy and balloon dilatation surgeries. In this study, we examined changes in neointimal stiffness in a Sprague-Dawley rat carotid artery intimal injury model and revealed that extracellular matrix (ECM) secretion and vascular stiffness were increased. Once the endothelial layer is damaged in vivo, activated platelets adhere to the intima and may secrete platelet-derived extracellular vesicles (pEVs) and communicate with vascular smooth muscle cells (VSMCs). In vitro, pEVs stimulated VSMCs to promote collagen secretion and cell adhesion. MRNA sequencing analysis of a carotid artery intimal injury model showed that ECM factors, including col8a1, col8a2, col12a1, and elastin, were upregulated. Subsequently, ingenuity pathway analysis (IPA) was used to examine the possible signaling pathways involved in the formation of ECM, of which the Akt pathway played a central role. In vitro, pEVs activated Akt signaling through the PIP3 pathway and induced the production of Col8a1. MicroRNA (miR) sequencing of pEVs released from activated platelets revealed that 14 of the top 30 miRs in pEVs targeted PTEN, which could promote the activation of the Akt pathway. Further research showed that the most abundant miR targeting PTEN was miR-92a-3p, which promoted Col8a1 expression. Interestingly, knockdown of Col8a1 expression in vivo abrogated the increase in carotid artery stiffness and simultaneously increased the degree of neointimal hyperplasia. Our results revealed that pEVs may deliver miR-92a-3p to VSMCs to induce the production and secretion of Col8a1 via the PTEN/PIP3/Akt pathway, subsequently increasing vascular stiffness. Therefore, pEVs and key molecules may be potential therapeutic targets for treating neointimal hyperplasia.